The Anti-tumoral Properties of Orexin/Hypocretin Hypothalamic Neuropeptides: An Unexpected Therapeutic Role - Couvineau, Alain; Dayot, Stéphanie; Nicole, Pascal; Gratio, Valérie; Rebours, Vinciane; Couvelard, Anne; Voisin, Thierry (Frontiers in Endocrinology, 2018)
Orexins (OxA and OxB) also termed hypocretins are hypothalamic neuropeptides involved in central nervous system to control the sleep/wake process which is mediated by two G protein-coupled receptor subtypes, OX1R and OX2R. Beside these central effects, orexins also play a role in various peripheral organs such as the intestine, pancreas, adrenal glands, kidney, adipose tissue and reproductive tract. In the past few years, an unexpected anti-tumoral role of orexins mediated by a new signaling pathway involving the presence of two immunoreceptor tyrosine-based inhibitory motifs (ITIM) in both orexin receptors subtypes, the recruitment of the phosphotyrosine phosphatase SHP2 and the induction of mitochondrial apoptosis have been elucidated. In the present review, we will discuss the anti-tumoral effect of orexin/OXR system in colon, pancreas, prostate and other cancers, and its interest as a possible therapeutic target.